PENINGKATAN AKTIVITAS BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN IPA DENGAN PENDEKATAN PROBLEM BASED LEARNING (PBL) DI KELAS V SDN 06 LIMBANANG KECAMATAN SULIKI - Yati Yati; Mudjiran Mudjiran; Yanti Fitria (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2020)
The background of this research is the lack of fifth students’ learning activities and critical thinking skills of science learning. This study aims to discuss and obtain data about the improvement of students’ learning activities and critical thinking skills in science learning with a problem-based learning (PBL) approach in grade 4 in a public elementary school in Suliki District. This type of research is classroom action research consisting of four stages, namely planning, action, observation, and reflection. This research consists of two cycles and the subjects in this study were 21 fifth grade students, consisting of 11 boys and 10 girls in 2016/2017 academic year. Data collection techniques used were observation sheets and tests. The data were analyzed using percentages and data reduction. The results showed that the implementation of problem-based learning (PBL) approach increased students’ learning activities and critical thinking skills in science learning which was marked by an increase of an average student's critical thinking ability from 69 in cycle I to 81 in cycle II.